2007
DOI: 10.1111/j.1365-2842.2006.01688.x
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration of anodized titanium implants under different current voltages: a rabbit study

Abstract: The oxide layer that covers a titanium surface is extremely stable and appears to have excellent biocompatibility, which can result in successful osseointegration. The aim of this study was to analyse the characteristics of an oxide layer formed by anodic oxidation (anodization), and to evaluate the extent of bone healing around the anodized implant. The screw-type implants were made of commercially pure titanium (Grade 2). The Group 1 samples had a turned surface, and three other types of experimental specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 25 publications
1
45
3
Order By: Relevance
“…This layer with approximately 5 nm thickness forms spontaneously in air or water and exhibits favorable thermodynamic properties, and low ion formation and electrical conductivity in the physiological environment 5 . The stability of the titanium oxide film depends strongly on its composition, structure and thickness 17 .…”
Section: Titanium In Biomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…This layer with approximately 5 nm thickness forms spontaneously in air or water and exhibits favorable thermodynamic properties, and low ion formation and electrical conductivity in the physiological environment 5 . The stability of the titanium oxide film depends strongly on its composition, structure and thickness 17 .…”
Section: Titanium In Biomaterialsmentioning
confidence: 99%
“…Also, the effects of nanotopographical on the bioactivity of titanium were studied in virto 55,70,[84][85][86][87][88] and in vivo 4,89,90 . Moreover, the growth of nanotube oxide was conducted on binary titanium alloys such as: Ti-Zr 91,92 , Ti-Nb 93 , NiTi 94 , ternary alloys such as: Ti-6Al-4V 5] , Ti-6Al-7Nb 6] and Ti-13Nb-13Zr 7 , and quarenty alloys like Ti-35Nb-xZr 7,98 , Ti-29Nb-xZr 7 nd Ti-35Nb-5Ta-7Zr alloy 5 .…”
Section: Some Studies On the Titanium Oxide Nanotubementioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, these approaches focused on the modification of the implant surface topography and morphology (17,18). These surface modifications mainly included mechanical methods such as machining (19,20), grinding, polishing (21) and blasting (22,23), and chemical methods such as acid etching (24,25), alkali etching (26,27) and anodization (28,29) to alter the topography of the titanium surface. Another approach towards the creation of a biologically active implant surface involves the application of an additional coating onto the titanium surface by means of physicochemical and biochemical deposition techniques (30,31).…”
Section: Surface Modification Of Titanium Implantsmentioning
confidence: 99%
“…This phenomenon also occurs on the surfaces of bioactive glass and glass ceramics [7,8]. Research showed that high degree of bone contact and bone formation was achieved with anodized titanium surface [9][10][11]. Saldana et al reported that the ability of human osteoblasts to differentiate when cultured on thermally oxidized titanium alloy [12].…”
Section: Introductionmentioning
confidence: 99%